Driving Productivity : Automation, Labor, and Industrial Development in the United States and Germany - Knowles, Anthony J., (Social Sciences E-Books Online, Collection 2026., 2025)
Driving Productivity reconstructs the industrial histories of the American and German automotive industries in a new light. From the Fordist assembly line to Japanese lean production and Industry 4.0, Anthony J. Knowles critically examines major technical developments within the historical dynamics of capitalism. Both countries face the pressure to automate, transform labor, and increase efficiency, yet their responses differ due to divergent paradigms of integrating business, labor, and government. Driving Productivity makes the case that improving productivity is a never-ending process that becomes a compulsory social imperative that industries must respond to but are nevertheless responded to differently between countries.